EFFECTIVENESS OF EXPERIENTIAL LEARNING MODEL TO INCREASE THE ANGER MANAGEMENT SKILLS IN ELEMENTARY SCHOOL STUDENTS - Nurvita, Desika Nanda (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2019)
The purpose of this research is to understand the effectiveness of experiential learning model tp increase the anger management skills in MI Miftahul Hidayah students. This research used one group pretest-posttest designs. The subjects of the research were taken from the students of grade of IV and V MI Miftahul Hidayah Gogourung with purpossive technique selection. Pretest result shows that there are eight students have low anger management score, then they were divided into a treatment group with experiential learning model. The research instrument uses anger management scale. The data analyzed by using Wilxocon sign rank test to verify the improvement of anger management in a group experiment. The result of the analysis indicates that a method used shows a significant increase the managing anger skill improvement.